The Development of Pempek Dos by using Chicken Liver as an Iron Fortification - Muhammad Basar, Firman; Pambudi Sujarnoko, Tekad Urip; Harpin Pranata, Rici Tri; Inayah Syahwani, Asty Khairi; Marithasari, Harries; Riski, Astari; Novinuryani Putri, Sosa; Syahwani, Asty (Jurnal Sosial Terapan, 2024)
One of the health problems that often occurs in young girls due to iron deficiency is anemia. Iron deficiency anemia can be prevented by using local food ingredients that contain high iron, namely chicken liver, which is substituted in the product pempek dos so that it becomes an iron fortified food. The research is aimed at developing a product of pempek with the addition of chicken liver. This study uses a complete random design (RAL) of one factor with three treatments. The results of the research showed that there was a significant difference in the hedonic test of color attributes. The chosen pempek formula is F2 with the addition of chicken liver 60 grams, F2 has an energy content of 346 kcal, protein 10.6 g, fat 5.7 g, carbohydrates 63.8 g, and iron 4.6 mg. This formula has a contribution to AKG as much as 16% energy, 16% protein, 8% fat, 21% carbs, and 30% iron.